Novas finanças: um estudo sobre a fragilidade da hipótese de mercados eficientes - Costa, Tiago Alves (2008)
The finance science, as all sciences, shows an evolutionary line and according to Kuhn (1970), it is marked by shortly periods of knowledge accumulation. However, according to the author, such periods are inserted with scientific revolutions. In other words, the scientific evolution is stamped by revolutions which abandon oldfashioned paradigm and create new ones. The revolution is followed by a period where the researches are guided by the new paradigm and its purpose is strengthen the own paradigm. In other way, the finance science has today a central paradigm well-known by efficiency market hyperlink (EMH) which was witnessed and adopted by the entire scientific community around the 70 s. And since those times, almost entire research done in finance, mainly until the de 90 s, was leaded and done to validate the EMH. This dissertation attempted to evidence that the finance evolutionary line proposed by Haugen (2000) follows the same principle evidenced by Kuhn (1970), and in the present-day, the EMH find itself in a period which precede the scientific revolution which is called by time crisis by Kuhn (1970). This time crisis could weaken the EMH and open a space to create a new paradigm. This way, the proposal of dissertation is to prove how the revolutionary process will happen in finance too, soon after, to prove what would the candidates more inclined to replace the EMH be as a central paradigm in finance. To do so, this work considered only two candidates: the behavioral finance and the chaos theory. To do this analyze it was used the schooling principles nominated by Mckinley, Mone and Moon (2002). Such authors propose that a thought must display a combination of novelty, continuity, and scope to achieve school status in organizational theory. The purpose of this dissertation is to do a theory ransom which intends to show the fragility of the EMH as a central paradigm that orients the finance researches. The dissertation concludes that the current finance faces a crisis, and in this period, the behavioral finance displays the biggest chance to replace the EMH in the near future, however, the chaos theory provides the bigger promise considering a far future